PREVENTING THE NEGATIVE EFFECTS OF THE COVID-19 EPIDEMIC IN INTERNATIONAL FREIGHT TRANSPORT - Vida, László; Illés, Béla; Bányainé Tóth, Ágota (Advanced Logistic Systems - Theory and Practice, 2021)
Measures taken to handle the COVID-19 epidemic in the spring of 2020 have had a significant impact on European supply chains. In terms of freight transport, this has led to a decline and congestion in truck traffic due to different restrictions on the internal borders of the EU. As similar situations cannot be avoided in the future, it is worthy to form supply chains that are less affected by different epidemics. Similarly to the physical internet hubs, distribution hubs can be forward-looking, but only if it helps development of rail-road intermodal freight transport. The article describes the possibility of a rail-road freight transport system that allows the application of radically new solutions through a new container handling technology that can be used in the rail-road relationship. The extension of the idea at the EU level could result in a significant increase in the share of rail freight and a sizeable reduction of the negative impact of epidemics on the supply chains. Among other effects, the solution can have a significant impact on the IT development of rail freight transport. The solution can also have effect to the development of the network of rail-road intermodal trans-shipment points, their automation and ultimately the completion of Logistics 4.0.